Bleeding Risk in Atrial Fibrillation Patients Taking Vitamin K Antagonists: Systematic Review and Meta‐Analysis. Issue 3 (13th May 2013) - Lopes, L C; Spencer, F A; Neumann, I; Ventresca, M; Ebrahim, S; Zhou, Q; Bhatnaga, N; Schulman, S; Eikelboom, J; Guyatt, G
<x xml:space="preserve">Abstract</x> Vitamin K antagonists (VKAs) prevent stroke in atrial fibrillation (AF) at the cost of bleeding risk. To determine major bleeding rates in AF patients, we conducted a systematic review that identified 51 eligible studies including more than 342, 699 patients. The pooled estimate of the rate of major bleeding was 2.51 (99% confidence interval: 2.03–3.11) bleeds per 100 patient‐years. The results represent the best estimates of bleeding risk that most patients contemplating VKA use may expect. Clinical Pharmacology & Therapeutics (2013); 94 3, 367–375. doi:10.1038/clpt.2013.99